(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract : The research aims to identify the importance of the repositioning strategy in rationalizing the costs of the Abu Ghraib dairy factory through the use of target cost technology, being an important tool in achieving rationalization, which facilitates the process of making pricing decisions for the factory’s products, and thus leads to achieving a competitive advantage that enables the plant to meet the challenges of the market, as the problem that most units operating in the Iraqi market suffer from is weak competition, due to the weakness of its traditional costing systems in providing information It helps in decision-making, and in order to test the hypothesis of the research, the Abu Ghraib dairy factory was chosen, as the research reached the possibility of rationalizing costs by applying the target cost technique to the factory’s products, which is reflected in achieving a successful repositioning strategy, which can lead to changing the competitive position of the factory for the better.